A Big Data Analytics Model for Household Electricity Consumption Tracking and Monitoring - Dollah R.; Aris H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Big data; Data Analytics; Electric power utilization; Energy utilization; Learning systems; Object oriented programming; BDA framework; Billing systems; Consumption patterns; descriptive analytics; Electricity-consumption; Evaluation results; Framework development; Household electricity consumption; Predictive analytics